Peran Manajemen Profit Dalam Mempengaruhi Laporan Keuangan Perusahaan - Ricgo Putra Andalas; Arya Satria; Ratih Kusumastuti (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This paper is intended to describe the responsibilities of managers in controlling how external reporting accounting policies are selected for reporting purposes. Earnings information is not misleading to investors. Yield management is goal oriented intervene in the external financial reporting process for the purpose of receiving a portion of the financial reporting; Private Interest (Schipper, 1989, 92). As a result, the ability to control the outcome You can't do away with your current accounting system. the problem is earning Management can influence investor decisions.